1980
DOI: 10.1111/j.1471-4159.1980.tb09001.x
|View full text |Cite
|
Sign up to set email alerts
|

Nervous System‐Specific Proteins in Developing Rat Cerebral Cells in Culture

Abstract: The nervous system-specific proteins; synaptin, D1, D2, D3, glial fibrillary acidic protein (GFA) and 14-3-2, were quantified in dissociated cerebral cells from the foetal rat brain at various times of growth in culture. By approximately 1 week in culture, the neuronal membrane markers synaptin, D1, D2, and D3 could all be demonstrated. A maximum concentration of 10-20% for synaptin, D1, and D3 and 160% for D2, in comparison with the levels in adult forebrain, was attained during the 2nd week in vitro. The ast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(13 citation statements)
references
References 26 publications
2
11
0
Order By: Relevance
“…They describe a monoclonal antibody (anti-BSP 2) recognizing the D2 antigen which labels the surface of different cerebellar cell types at different stages of cerebellar development. Still in cultures of cerebellar interneurones anti-BSP 2 exclusively labels neurones (Hirn et al,198 I) in agreement with the exclusive neuronal localization in brain cell cultures described by others (Bock et al, 1980;Meier et al, 1982). Thus such primary cultures may offer a more simple system for the study of the role of D2 on the neuronal surface membrane and thereby may prove valuable for the elucidation of the functional importance of D2 for neuronal development in vivo.…”
Section: E Meier Et Alsupporting
confidence: 67%
“…They describe a monoclonal antibody (anti-BSP 2) recognizing the D2 antigen which labels the surface of different cerebellar cell types at different stages of cerebellar development. Still in cultures of cerebellar interneurones anti-BSP 2 exclusively labels neurones (Hirn et al,198 I) in agreement with the exclusive neuronal localization in brain cell cultures described by others (Bock et al, 1980;Meier et al, 1982). Thus such primary cultures may offer a more simple system for the study of the role of D2 on the neuronal surface membrane and thereby may prove valuable for the elucidation of the functional importance of D2 for neuronal development in vivo.…”
Section: E Meier Et Alsupporting
confidence: 67%
“…No further change in the average amount of GFAP was observed up to 78 DIV (latest time studied). The concentration of GFAP in these cul tures is similar to that demonstrated in cul tures of dissociated cerebral cells from fetal or newborn rats or mice [4,24,25,29].…”
Section: Immunocytochemistrysupporting
confidence: 48%
“…The second phase was distinguished by a relatively higher content of GM3 and GD3 and of the disialogangliosides GDla and GDlb. These data are in favor of a glial origin, as demonstrated by TEM and by the use of one of the better astrocyte markers, ie, GFAP [Pfeiffer et al, 1977;Bignami et al, 1980;Bock et al, 1980;Stieg et al, 19801, the newly demonstrated oligodendrocyte marker; ie, CAI1 [Vincendon et al, 19781, UDP-ga1actose:ceramide galactosyltransferase cerebroside and monogalactosyl diacylglycerol sulfotransferases [Sarlike et al,198Odl of the cells encountered during that phase.…”
Section: Discussionmentioning
confidence: 99%